Piper betle stem extract induces apoptosis through mitochondria inactivation, p38MAPK activation and ErB2/ErbB3 suppression on oral squamous cell carcinoma cells - Meng-Tse Lee; Chi-I Chang; Jen-Jie Lin; Yu-Jen Wu (Elsevier, 2022)
Background: Oral cancers are a group of carcinomas that appear in the oral cavity. The cause of oral cancer is still unclear. However, betel nut chewing, smoking and drinking alcohol are all known risk factors for oral cancers, among which the habit of chewing of betel nuts is known to be associated with the highest risk of oral cancer. Hypothesis/Purpose: This study aimed to examine the mechanisms of anti-cancer effects of the Piper betle (P. betle) stem. Methods: In this study, MTT assays, cell morphology analysis and flow cytometry were employed to evaluate the anti-cancer effects of an extract of the P. betle stem on human oral squamous cell carcinoma cell lines Cal-27 and Ca9-22. Potential effects on cell proliferation and apoptotic molecular mechanisms were evaluated by western blotting. Results: Treatment with P. betle stem extract inhibited cell proliferation in Cal-27 and Ca9-22 cells, and its effect on cell growth was mediated by a mechanism associated with apoptosis. The apoptotic cell death involved mitochondrial inactivation, causing downregulation of the expressions of Bcl-2 and Bcl-xl and increasing the expressions of Bax and Bad. Activation of p38MAPK and inhibition of the expressions of ErbB2 and ErbB3 were also involved in the P. betle stem extract-induced apoptosis in oral cancer cells. Conclusion: The findings from this study indicated that crude extract of the P. betle stem may regulate signaling pathways via apoptosis, suggesting that this extract has great potential for development as a new drug for the treatment of oral cancer.